Laughing About and With the Absurd in Twentieth-Century German Literature: With a Focus on Kurt Kusenberg - Classen, Albrecht (Cultural Arts Research and Development, 2025)
Since the early twentieth century, intellectuals, artists, writers, and philosophers across the board have realized that humanity is increasingly losing its grip on its own existence in many different terms. Neither rationality nor reality seems to make all that much sense any longer. Catastrophic experiences in various wars, in the Holodomor, Holocaust, and a long series of other genocidal campaigns across the world, and now the virtually certain prospect that we humans are causing global warming and hence threaten to destroy the foundation of our existence here on earth increasingly indicate that the traditional rational framework is fraying at its seams and threatens to undermine the core of our existence. Since the early twentieth century, we have observed the growth of absurdity as a new mode of expression. Whereas scholarship has so far focused mostly on such famous writers as Franz Kafka, Albert Camus, or Jean-Paul Sartre, this article introduces a different approach to absurdity through the lens of satire and the grotesque, intriguingly represented by the German author of short stories, Kurt Kusenberg. As much as he made his audience smile, if not even laugh about the absurd conditions in ordinary human situations, basically their own, he deftly, though subtly, indicated that for him as well absurdity had become the norm of human life. Yet there is no way to combat it, as the author suggests; instead, mocking absurdity offers healthy, productive alternatives beyond traditional efforts to operate with a rational epistemology and to laugh about absurdity itself.